Friendly Science: Medical, Scientific, and Technical Amici Before the Supreme Court - Stephanie Tai (Washington University Law Quarterly, 2000)
This Article examines the participation of medical, scientific, and technical organizations, as well as individuals in a medical, scientific, or technical capacity, as amici before the Supreme Court. This examination is limited to organizations’ and individuals’ participation as parties on amicus curiae briefs. Part II discusses the general role of amici before the Supreme Court, as well as scientific and technical information currently presented to the Court. This Part then briefly introduces and critiques the Court’s use of scientific and technical information as “legislative facts”— legally significant facts that transcend a particular dispute yet are still relevant to the legal reasoning involved in the dispute—providing examples of cases where the Court has used “legislative facts” both inside and outside the context of science. This Part argues that there are two reasons why the scientific and technical amici participation is important when the Supreme Court adjudicates in technical and scientific areas. First, the information and expertise—especially regarding the scientific process as well as particular scientific facts—provided by scientific and technical amici are necessary for the Court to appreciate fully the consequences at stake in a particular case. Second, the information and their expertise are necessary for the public to contextualize the Court’s rulings. Part III describes what parties are considered scientific or technical amici within the scope of this paper, and lays out the methodology used to conduct research on those parties’ amicus briefs. Part IV explores actual amicus curiae briefs of medical, scientific, and technical amici. This Part addresses the characteristic factors examined for each amici participant and each amicus brief and also presents the results of this study of ninety-two medical, scientific, and technical organizations and individuals that have been amici before the Supreme Court in the last decade. Particularly, this study exposes the relative predominance of medical organizations as amici and the relative absence of medical, scientific and technical amici in environmental cases. Part V of this Article then considers possible explanations for the disparity between medical, scientific, and technical amici participation. These explanations include the nature of the Supreme Court docket and varying levels of attorney familiarity with scientific and technical amici. The relative absence of scientific and technical amici in environmental cases is especially notable because environmental cases have similar characteristics to health and medical cases in which the Court found scientific and technical, as well as medical amici participation useful. Consequently, this Article addresses the value that scientific and technical organizations add as amici in environmental cases. In particular, it examines the role that they did play in informing the Court about scientific issues in American Trucking Associations, Inc. v. EPA, as well as additional roles that they could have played. In American Trucking, amici briefs by scientific organizations will aid the Court by presenting critical information about the nature of risk assessment, although more participation would have been helpful for the Court’s full resolution of the scientific issues involved. Part VI concludes that scientific and technical amici can participate in ways valuable to the Court when the dispute allows these amici to present information relevant to their technical or scientific expertise. Because environmental cases frequently involve scientific and technical matters, this Article urges scientific and technical organizations to increase their participation as amici in these cases to enable the Court to maintain a consistent level of informed decision making in all environmental cases involving scientific and technical issues.
Keywords: Amici curiae; Science; Environmental law; Judicial statistics; United States. Supreme Court; Legal briefs; Scientific evidence (Law)